Best man rancher [large type] - Yates, Maisey (Yates, Maisey. Carsons of Lone Rock, 2023)
"Being his brother's best man is a privilege for Kit Carson. The rancher likes his future sister-in-law . . . and he really likes her sister, Shelby Sohappy. Now that he and Shelby are thrown together for wedding preparations, Kit can finally make his move. Shelby is still grieving her husband, so his offer is just one night with no strings -- he knows her heart can't handle more. Kit is certain he's fine with that . . . until he isn't. And now Shelby's expecting. Can the best man prove he's the man for Shelby?"--